Adult Intensive Care Unit antimicrobial Stewardship program: An integrative review (Research, Society and Development, 2024)
ICU patients are more likely to acquire health-related infections due to their severe clinical condition and the inappropriate use of antimicrobials, which can lead to increased bacterial resistance. In this context, a strategy for the control of bacterial resistance is Antimicrobial Stewardship defined as coordinated interventions to reduce the inappropriate use of antimicrobials, reduce the development of resistance and reduce costs. Objective: To conduct an integrative review on the application of antimicrobial stewardship to clinical and economic outcomes of adult ICU patients. Methodology: This review adopted the PICo strategy to ask the question "What improvements can the antimicrobial stewardship program bring to adult intensive care units?" The following databases were used: LILACS, PubMed Central, SCOPUS, EMBASE, WEB OF SCIENCE, SCIENCE DIRECT and MEDLINE, with articles published in English between 2018 and 2023. The DeCS and MeSH descriptors were: "Intensive Care Units", "Antimicrobial Stewardship", "Drug Resistance, Bacterial", "Infection Control”. Results: Twelve studies were in agreement with the established inclusion criteria and demonstrated that adherence to the interventions proposed by the Antimicrobial Stewardship Program is associated with a decrease in the time and doses of antibiotic therapy, in addition to stimulating rational use in the ICU. Conclusion: The Stewardship Program for Antimicrobials in adult ICUs brings benefits in reducing bacterial resistance and the use of antimicrobials. Consequently, reducing hospital costs, with the pharmacist being the key player in the strategy for the rational and safe use of antimicrobials.